The politics of boarding: promotion of selected Muslim writers in Malaysia, Indonesia and Brunei - Abdul Manaf, Nor Faridah (s.n, 2012)
This paper investigates to what extent the publishing world, media and selection of the winners of literary prizes are ideology free by analysing scholars’ observations on the matter and studying controversies that arise among the writers themselves. The paper studies a selected sample of Southeast Asian writers who write in their mother tongue (either in Malay, Bahasa Indonesia or Bahasa Brunei). Not much is known of writings of these writers and this paper is an attempt to understand the other world which is often seen as a rival to the English-writing world. A number of famous writers and various recipients of many literary prizes in Malaysia, Brunei and Indonesia were interviewed and their perceptions would be shared in this paper. This paper analyses to what extent the literary world is influenced by cultural capital through the politics of branding which is channeled through publishers’ ideology, and the hidden agenda of media and literary awards. These hypotheses and assumptions may invite public anger, but the politics of branding or the hidden agenda of the media (media agenda-setting) is not something new. Controversies arising about the awards is also not something we have never heard of. The main purpose of this paper is to examine issues related to the politics of branding and to investigate the extent of how ideology-free publishing, media and literary prize organisers are in the Malay archipelago taking into account the views of some scholars and writers from three Southeast Asian countries namely Malaysia, Brunei and Indonesia.